2007
DOI: 10.1088/1475-7516/2007/01/012
|View full text |Cite
|
Sign up to set email alerts
|

Non-saturated holographic dark energy

Abstract: It has been well established that holographic dark energy (HDE) is a serious candidate for being the dark energy of the universe. Here we deal with models where the holographic bound for dark energy is not saturated for a large portion of the history of the universe. This is particularly compelling when the IR cut-off is set by the Hubble scale, since otherwise a transition from a decelerated to an accelerated era cannot be obtained for a spatially flat universe. We demonstrate using three generic but disparat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
96
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 17 publications
4
96
0
Order By: Relevance
“…To avoid the breakdown of the local quantum field theory, Cohen et al [5] suggested a more restrictive bound. They proposed that the entropy for an effective quantum field theory ∼ L 3 Λ 3 should satisfy [5,6]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid the breakdown of the local quantum field theory, Cohen et al [5] suggested a more restrictive bound. They proposed that the entropy for an effective quantum field theory ∼ L 3 Λ 3 should satisfy [5,6]…”
Section: Introductionmentioning
confidence: 99%
“…(1) or (2), it is easy to find that ρ Λ ∼ < m 2 p L −2 . In [6], there is an alternative derivation of HDE by invoking the Bekenstein bound. For a macroscopic system in which self-gravitation effects can be disregarded, the Bekenstein bound S B is given by the product of the energy E ∼ ρ Λ L 3 and the linear size L of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical aspects of the holographic dark energy have been studied extensively in the literature, see [30,31,32,33,34,35,36,37,73,74,75,76] for examples. Also, the holographic dark energy has been tested and constrained by various observations, such as SNe Ia [38], CMB [39], X-ray gas mass fraction of galaxy clusters [40], the differential ages of passively evolving galaxies [41], Sandage-Leob test [42], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The HDE model based on the entropy bound can be also derived with a different approach [61]. In the black hole thermodynamics [62,63], a maximum value of the entropy in a box with a dimension of L (which is also referred as Bekenstein-Hawking entropy bound), exists and it is given by…”
Section: Introductionmentioning
confidence: 99%